Pengaruh Gaya Kepemimpinan terhadap Motivasi dan Dampaknya terhadap Kinerja Sumber Daya Manusia - Resky Resky; Engkos Achmad Kuncoro (Binus Business Review, 2012)
PT Bukit Asam (Persero) Tbk (PTBA) is a state-owned companies in the field of the largest coal mine in Indonesia. The purpose of this study was to determine how much influence the leadership style to employee motivation human resource Human Resources Division, how much influence employee motivation to employee performance Human Resources Division Human Resources Division and how much influence the style of Leadership Human Resources Division directly or indirectly against employees HR Human Resources Division office Tanjung Enim mining center unit PTBA. The method in this study is associative with the design of the study through the survey method by distributing questionnaires to the respondents by simple random sampling and data processed with SPSS 17.0 software. From the results of research studies can be explained that the leadership style that has a positive and significant impact on employee motivation high and low HR Division PTBA directly with the influence of (0.349) 2 = 12.18%, as well as motivation to have a positive and significant  influence of high low level of employee performance PTBA Human Resources Division directly, further direct leadership style has positive and significant impact on employee performance PTBA Human Resources Division and influential leadership style indirectly through employee motivation to the Human Resources Division kenerja PTBA.